The role of stakeholders in shaping managerial perceptions of CSR in Russia. (7th May 2010) - Kuznetsov, Andrei; Kuznetsova, Olga
This paper investigates the sources of socially responsible behaviour of firms with reference to a survey of managers of medium and large firms in Russia. We argue that agency-oriented analysis is not a good fit for the institutional environment existing in Russia. Consequently, a meaningful management-stakeholder dialogue acquires particular importance. Our results offer some support to the proposition of a link between the interests of the dominant stakeholder and the interpretation of corporate social responsibility entertained by the management of the firm. However, more data are needed to increase the accuracy of results.